PENGEMBANGAN WEBSITE STUDIKU BERBASIS OPEN EDUCATIONAL RESOURCES (OER) RAMAH ANAK PADA PEMBELAJARAN BAHASA INDONESIA DI SEKOLAH DASAR - Dwiyanita, - (2023)
Penggunaan dwibahasa atau code mixing (campur kode) antara bahasa Indonesia dan bahasa daerah seringkali dijumpai dalam proses pembelajaran di sekolah dasar. Penelitian ini dilakukan untuk menghasilkan media pembelajaran website Studiku berbasis Open Educational Resources (OER) ramah anak pada pembelajaran Bahasa Indonesia yang dapat diakses melalui ponsel. Perbendaharaan kata bahasa Indonesia tentunya dapat menunjang proses komunikasi siswa dengan lingkungan sekitarnya. Kurangnya ketersediaan bahan ajar bahasa Indonesia di sekolah dasar membuat literatur siswa untuk menambah kosakata dari berbagai bacaan juga semakin sedikit aksesnya. Oleh karena itu, guna menunjang peningkatan perbendaharaan kata dan kemampuan berbahasa Indonesia siswa sekolah dasar maka perlu adanya media pembelajaran yang memuat bahan ajar di dalamnya yang dapat diakses secara cepat dan mudah. Metode penelitian menggunakan penelitian pengembangan dengan model Design and Development Type 1. Prosedur Penelitian menggunakan alur penelitian Design and Development Type 1 yaitu analysis, product design and development, validation of tool and technique, dan product evaluation. Hasil uji kelayakan website Studiku oleh validator ahli materi dan bahasa, serta validator ahli media memperoleh rata-rata skor 87,08% dengan kriteria "Sangat Layak" untuk digunakan pada pembelajaran bahasa Indonesia kelas IV di sekolah dasar. Respons pengguna yaitu sekolah, instruktur, guru, dan siswa menunjukkan respons positif terhadap penggunaan website Studiku dalam proses pembelajaran. Implikasi website Studiku ini sebagai media pembelajaran yang memuat bahan ajar bahasa Indonesia bagi siswa kelas IV sekolah dasar dan sebagai media untuk memperkaya perbendaharaan kata siswa. -------------- The use of bilingualism or code mixing between Indonesian and regional languages is often found in the learning process in elementary schools. This research was conducted to produce learning media for the Studiku website based on child-friendly Open Educational Resources (OER) for learning Indonesian which can be accessed via a cellphone. Indonesian vocabulary can certainly support the student's communication process with the surrounding environment. The lack of availability of Indonesian language teaching materials in elementary schools means that students have less access to literature to add to their vocabulary from various readings. Therefore, in order to support the increase in the vocabulary and Indonesian language skills of elementary school students, it is necessary to have learning media that contains teaching materials that can be accessed quickly and easily. The research method uses development research with the Design and Development Type 1 model. The research procedure uses the Design and Development Type 1 research flow, namely analysis, product design and development, validation of tools and techniques, and product evaluation. The results of the Feasibility Test on the Studiku website by material and language expert validators, as well as media expert validators obtained an average score of 87.08% with the "Very Eligible" criteria for use in Indonesian language learning for grade IV in elementary schools. User responses, namely schools, instructors, teachers, and students, show a positive response to the use of the Studiku website in the learning process. The implications of this Studiku website as a learning medium that contains Indonesian language teaching materials for fourth grade elementary school students and as a medium to enrich students' vocabulary.